Factors Influencing Consumers’ Purchase Behaviour towards Green Packaged Products - Ling, Goh Mei; Tiep, Ho Sew; Fern, Yeo Sook; Lun, Teh Wei (RSF Conference Series: Business, Management and Social Sciences, 2025)
The disposal of plastic packaging has caused the amount of waste generation, which have a negative impact on the environment. Green packaging, which is more eco-friendly packaging, is harmless to human health and biodegradable. Many businesses have turned to the movement of going green by providing green products and services. Hence, the objective of this study is to investigate the factors that influence the purchase behaviour of consumers towards green packaged products. A total of 200 respondents was recruited using convenience sampling. Data were collected with a set of self-administered questionnaires that covered respondents' profiles and all the variables in the research model. Partial Least Square Structural Equation Modeling was used to assess the measurement model and structural model. Both convergent validity and discriminant validity were deemed satisfactory. The findings have revealed 0.444 of R2 means that the model explains 44.4% of the total variation of purchase behaviour. Environmental concern and environmental attitude were found to affect consumers’ purchase behaviour positively towards green packaged products. Environmental knowledge and social influence, however, were found to be non-significant. This study will be able to provide valuable information to the marketers to focus not only on their products but the packaging of their products as well. This study also provides an insight into the consumers’ purchase behaviour towards green packaged products. It is recommended for future research to recruit more respondents with a more diversified background.